The Enterprise, a massive transposon carrying Spok meiotic drive genes - Vogan, Aaron A.; Ament-Velásquez, S. Lorena; Bastiaans, Eric; Wallerman, Ola; Saupe, Sven J.; Suh, Alexander; Johannesson, Hanna (Genome Research, 2021)
The genomes of eukaryotes are full of parasitic sequences known as transposable elements (TEs). Here, we report the discovery of a putative giant tyrosine-recombinase-mobilized DNA transposon, Enterprise, from the model fungus Podospora anserina. Previously, we described a large genomic feature called the Spok block which is notable due to the presence of meiotic drive genes of the Spok gene family. The Spok block ranges from 110 kb to 247 kb and can be present in at least four different genomic locations within P. anserina, despite what is an otherwise highly conserved genome structure. We propose that the reason for its varying positions is that the Spok block is not only capable of meiotic drive but is also capable of transposition. More precisely, the Spok block represents a unique case where the Enterprise has captured the Spoks, thereby parasitizing a resident genomic parasite to become a genomic hyperparasite. Furthermore, we demonstrate that Enterprise (without the Spoks) is found in other fungal lineages, where it can be as large as 70 kb. Lastly, we provide experimental evidence that the Spok block is deleterious, with detrimental effects on spore production in strains which carry it. This union of meiotic drivers and a transposon has created a selfish element of impressive size in Podospora, challenging our perception of how TEs influence genome evolution and broadening the horizons in terms of what the upper limit of transposition may be.